Anticipated fertilization and fertilizer distribution ways on maize seeding (Research, Society and Development, 2021)
Anticipation and spreading of fertilizer increase the operational efficiency of maize sowing by eliminating the supply of fertilizer in the sowing machine. This work aimed to study the anticipation and ways of fertilization of maize sowing in order to increase operational efficiency, and performance of agronomic attributes with fertilization by haul after sowing followed by the distribution of straw over the soil surface in no tillage system (no-till). The experiment was carried out at the Teaching, Research and Extension Farm of Ilha Solteira-UNESP in Selvíria, Mato Grosso do Sul, Brazil. The maize cultivar chosen was VT PRO 2. It was used a randomized block design, with 10 treatments: residual effect of the stem, fertilizer spreading 30 days before sowing (DBS) and on the day; fertilizer spreading 30 DBS and in the day; fertilizer spreading and vegetation management with a horizontal straw crusher; incorporation of the fertilizer with stem or disk 30 DBS and sowing day; residual effect of the stem sown without fertilizer and sowing without fertilizer. Dry mass of plants, grain yield and other variables were analyzed. Grain productivity was similar between treatments. Plant dry mass production was higher with the crusher. Grain productivity is the same in the distribution modes and fertilizer application period in no-till, early fertilization by haul at 30 days increases the operational efficiency of sowing. The use of the crusher increases the dry mass of plants production in no-till.